Evaluation of Micropiles With Different Configuration Settings for Landslide Stabilization Based on Large-Scale Experimental Testing - Liu, Xueling; Yan, Jinkai; Tong, Bin; Liu, Lei (Frontiers in Earth Science, 2021)
In this study, a large-scale model test was performed to investigate the effect of the single-row and double-row micropiles on the landside stabilization. For two different testing configuration settings, the bending moment along the micropiles, failure mode, and force condition were captured and compared. It is found that the landslide thrust on piles was distributed in a triangular shape. The piles in the front row carried greater pressure than the piles in the rear row. The resistance of the sliding body behind the pile was distributed in a parabolic shape, and mainly concentrated on the middle of the pile. The piles were destroyed due to the combined shearing and bending impact applied near the slipping surface. The boundary of the failure zone was from the position of two times the pile diameter under the slipping surface to the position of two and a half times the pile diameter above the slipping surface. Under the action of the landslide, each row of piles deformed at the same time. The capability of landslide stabilization for double-row piles was better than that of a single-row pile. The sections of the pile above slide surface were mainly subjected to negative bending moments and were distributed mainly within the pile length range of one-third of the anti-sliding section above the sliding surface. The pile body of the embedded section located in the range of ten times the pile diameter below the sliding surface was subjected to a positive bending moment.